A canção Todo o sentimento, de Chico Buarque e Cristovão Bastos: um exercício de leitura verbo-musical - Marcio Ronei Cravo Soares (2007)
Interpretive analysis on the popular song Todo o sentimento (All the feeling) by brazilian composers Chico Buarque and Cristóvão Bastos, departing from the following primary sources: its recording in the album Francisco (BUARQUE, 1987); its musical transcription published in Songbook Chico Buarque (CHEDIAK, 1999); the leadsheet of Chico Buarques interpretation in the album Francisco and an interview with Cristóvão Bastos, co-author of Todo o sentimento, transcribed in the Appendixes of this study. The verbal and musical texts, unalienable components of a song, will be studied in the light of theoretical references by TATIT (2002b), ULHÔA (1999), PAZ (1972),GOLDSTEIN (1999) and BARTHES (1985). The aim of this study is torecognize connections between the verbal and the musical discourses, whose integration seems to present a relation of reciprocity.